Alcohol consumption among adolescents during the Covid 19 pandemic, Convid Adolescents – Behavior Research - Malta, Deborah Carvalho (2022)
Objective: To describe the prevalence of alcohol consumption before and during the Covid 19 pandemic and to analyze the factors associated with this behavior during the period of social distancing in Brazilian adolescents. Methods: Cross-sectional study, using data from the Convid Adolescents survey, carried out via the web between June and September 2020. The prevalence of alcohol consumption before and during the pandemic and association with sociodemographic variables, mental health, lifestyles was estimated. A logistic regression model was used to assess associated factors. Results: 9,470 adolescents were evaluated. Alcohol consumption decreased from 17.70% (95%CI: 16.64;18.85) before the pandemic to 12.80% (95%CI: 11.85;13.76) during the pandemic. Higher alcohol consumption was associated with the age group of 16 and 17 years (OR=2.9;1.08-1.53), living in the South region (OR=1.82;1.46;2.27) and Southeast (OR=1.33;1.05;1.69), having 03 or more close friends (OR=1.78;1.25;2.53), reporting worsening sleep problems during the pandemic (OR=;1.59;1.20;2.11), feeling sad sometimes and always (OR=2.27;1.70;3.05), always irritated, being a smoker (OR=13, 74;8.63;21.87) and passive smoking (OR=1.76;1.42;2.19) were associated with higher alcohol consumption. Adherence to the restriction in a very strict way was associated with lower alcohol consumption (OR=0.40;0.32;0.49). Conclusions: The pandemic caused by Covid 19 led to a decrease in the consumption of alcoholic beverages by Brazilian adolescents, being influenced by sociodemographic and mental health factors, adherence to social restriction measures and lifestyle. It is necessary to involve managers, educators, family and society in the articulation of Public Policies for the prevention of alcohol consumption.